Comparison between wharton’s jelly and collagen natural hydrogels for human ovarian follicle transplantation as an artificial ovary - Farnaz Tajbakhsh; Mohammad Kazemi Ashtiani; Somayeh Tavana; Ashraf Moini; Rouhollah Fathi (PLoS ONE, 2025)
Artificial ovary (AO) is a bioengineered approach aimed at increasing fertility potential in certain cases, especially in women and prepubertal girls with a history of cancer. Some natural and synthetic materials can be used for ovary bioengineering. In the current study, we compared two natural hydrogel composites containing alginate (Alg): Wharton’s Jelly (WJ/Alg) and Collagen (Col/Alg) as models for human AO. In total, six experimental groups were designed: WJ/Alg, Col/Alg, WJ/Alg +FSH , Col/Alg +FSH , WJ/Alg +EPO , and Col/Alg +EPO (n = 60). In each group, 40 isolated human ovarian follicles were seeded in 10 µl of the desired hydrogel and xenotransplanted into the right side of the peritoneum in ovariectomized NMRI mice for 1 week. FSH (7.5 IU) and Erythropoietin (EPO; 200 IU/kg as an angiogenic factor) were injected every other day. Histological and immunohistochemical assessments for Vimentin, CD45, and Ki67; Gene expression analysis for GDF9 , Vegf, and CD45 ; and hormonal assays for estradiol and progesterone were performed. Histological staining showed that WJ/Alg can support follicle growth. In contrast, most of follicles in Col/Alg remained at the primordial stage. Although FSH injection helped granulosa cells differentiation, especially in the WJ/Alg group (507.6 ± 134.1 vs 1444 ± 493.6), and EPO injection increased blood vessels in both groups ( p -value<0.0001), the follicles could not preserve in the experimental groups. In addition, there were no significant differences in gene expression and hormonal assays across all groups. Based on the histological analysis, the WJ/Alg-base artificial ovary provided better support for follicle development after 1 week compared to the other groups. In addition, Adjusting FSH and EPO dosage may improve follicle survival and growth in future studies.